John Winthrop : America's forgotten founding father - Bremer, Francis J. (OUP E-Books., 2003)
Vividly paints the life of John Winthrop as a disappointed and disaffected member of the English elite, examining how and why Winthrop and others decided to cross the Atlantic and found the Massachusetts Bay Colony. This book shows how Winthrop developed the skills to become the first governor of the colony.